2017
DOI: 10.1021/acs.organomet.7b00426
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Potent Antibacterial Agent Targeting Methicillin-Resistant Staphylococcus aureus Based on Cobalt Bis(1,2-Dicarbollide) Alkoxy Derivative

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a notorious superbug that is potentially lifethreatening. Among conventional antibiotics, vancomycin is a "gold standard" agent used to treat serious MRSA infections. Such therapy, however, is often ineffective because of the emergence of less-susceptible strains. Therefore, the exploration of new antimicrobial agents, especially nonantibiotic drugs, to cope with the growing threat of MRSA has become an urgent necessity. Herein, we have investigated the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 52 publications
3
50
0
Order By: Relevance
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AuDAMP also can fight mutli-drug resistant bacteria such as E. coli , Acinetobacter baumannii (A. baumannii) , Pseudomonas aeruginosa , Klebsiella pneumonia (K. pneumonia) , methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecium (E. faecium). To kill bacteria, the mechanisms of antimicrobial AuDAMP have been demonstrated by the combination of cell membrane destruction, DNA damage and ROS generation caused by AuDAMP to bacteria (Figure 5) [95,96,97].…”
Section: Small Molecule-conjugated Auncsmentioning
confidence: 99%
“…The isomers of the closo-C2B10H12: ortho-(1,2), meta-(1,7), or para- (1,12); as well as nido-[C2B9H12]isomers: ortho-(7,8) and meta-(7,9). to obtain the hexaanion [1,2,8,9,10,12{3,3 [111] Li [112] Na [108] Na3 [109] Thiam. Significantly lower MICs versus wide-spectrum antibiotic thiamphenicol (used as positive control) are presented as follows: *P < 0.05, **P < 0.01, ***P < 0.001 vs. thiamphenicol Table 5.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…[111] Recently, it has been reported that [3,3'-Co(8-CH3CH2O)2-1,2-C2B9H10)(1',2'-C2B9H11)]has a high bacteria-killing efficiency observed with eradication of all TSA MRSA cells within 30 min. [112] More importantly, unlike the vancomycin antibiotic, a repeated treatment with [3,3'-Co(8-…”
mentioning
confidence: 99%